7 - Husbands in Wives’ Shoes: Changing Social Roles in Child Care among Cameroon’s Urban Residents - Kam Kah, Henry (Africa Development, 2021)
Childcare has for a long time been the near exclusive responsibility of women and female house mates in Cameroon and other parts of Africa but contemporary urban challenges have forced many of these women and house mates to engage in activities that limit their ability to fully devote time to child care especially in urban contexts. There is also a growing change in social attitudes among males that has led to a blurring of traditional gender roles. As a result, some aspects of children’s care have devolved to husbands or fathers. This paper challenges existing orthodoxies regarding gender roles by explaining new developments in child care by fathers among urban residents in Cameroon. What factors explain the increasing role that men are playing in the caring of their children and what implications do they have for household development and society? This paper addresses these issues using historical, anthropological, psychological and sociological methods and techniques of data collection and analyses.